Influências do tamanho da semente de soja na qualidade fisiológica - Costa, Sérgio Moacir Dalla (2006)
The soybean (Glycine max L. Merril) nowadays, in Brazil, is the species with biggest extension of cultivation and with a relevant economic importance in the country. So, it becomes fundamental to know all of factors that involve the germinative process of soybean seed, aiming a higher economic success since the sowing. The use of efficient procedures to evaluate the physiologic quality is fundamental in control programs of quality. The present work had the objective of evaluate the physiological quality of soybean seeds, classified in different sizes, the distribuition of seeds about the size and wheight of a thousand of seeds. To evaluate the quality, germination tests, accelerated aging tests and emergency test of plants in the field was realized. The search was realized in Cascavel, Paraná State in the 2004/2005 years at Coopavel Cooperativa Agroindustrial with soybean seeds from CD 202 e CD 215 cultivars, classified in four sizes of seeds (5,5; 6,0; 6,5 and 7,0mm). The experimental lineation used was the blocks entire casualized. It was not observed the effect of the sizes of seeds in the physiological quality of seeds in the two cultivars. The parcel of CD 215 cultivar presented superior physiological quality than the cultivar parcels of CD 202.